2021
DOI: 10.3390/cryst11030232
|View full text |Cite
|
Sign up to set email alerts
|

Use of Recycled Concrete Aggregates in Production of Green Cement-Based Concrete Composites: A Review

Abstract: Recycled concrete aggregates (RCA) are used in existing green building composites to promote the environmental preservation of natural coarse aggregates (NCA). Besides, the use of RCA leads to potential solutions to the social and economic problems caused by concrete waste. It is found that insufficient information on the longevity and sustainability of RCA production is a serious issue that requires close attention due to its impact on changing aspects of the sector. However, more attention has been paid to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
54
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

4
5

Authors

Journals

citations
Cited by 103 publications
(56 citation statements)
references
References 167 publications
1
54
0
1
Order By: Relevance
“…The optimum compressive strength was 93 MPa [ 189 ]. In a previous study [ 241 ], recycled coarse aggregate (RCA) obtained from crushed structural concrete beams and clay was utilized in FA-based AAM to produce concrete with adequate mechanical characteristics [ 197 , 241 , 242 , 243 ]. It was reported that AAM with RCA developed a less compressive strengths of up to 10.3 MPa compared to that with natural coarse aggregates [ 241 ].…”
Section: Mechanical Propertiesmentioning
confidence: 99%
“…The optimum compressive strength was 93 MPa [ 189 ]. In a previous study [ 241 ], recycled coarse aggregate (RCA) obtained from crushed structural concrete beams and clay was utilized in FA-based AAM to produce concrete with adequate mechanical characteristics [ 197 , 241 , 242 , 243 ]. It was reported that AAM with RCA developed a less compressive strengths of up to 10.3 MPa compared to that with natural coarse aggregates [ 241 ].…”
Section: Mechanical Propertiesmentioning
confidence: 99%
“…Concrete is an extraordinary composite material, widely used in the construction industry. It consists of a mix of fine and coarse aggregates bonded together with cement paste [1,2]. Evaluating the performance of cement is a very challenging task because it changes significantly when it comes into contact with water [3].…”
Section: Introductionmentioning
confidence: 99%
“…From this equation, by using geotechnical equipment under static conditions, the inherent forces likes cohesion and friction occur due to the abrasion of particles. The formula used to measure the cohesive force is given by Equation (1).…”
Section: Introductionmentioning
confidence: 99%
“…For this, the absorption and insulation of sound were checked at different frequencies on rubber concrete. Concrete specimens were meant to replace the 0 to 100% coarse aggregate with two recycled tires rubber aggregates, up to 60% of the overall concrete volume [124][125][126][127][128]. Furthermore, concrete panels were cast with various surface finishes (rough and smooth surface) to evaluate the influence of the external texture and the direct contact of rubber [129].…”
Section: Cellular Concretementioning
confidence: 99%